Congressional capacity and the abolition of legislative service organizations. (15th November 2018) - Clarke, Andrew J.
Abstract: I analyse the relative influence of lawmakers before and after a watershed moment in the development of faction institutions: the abolition of legislative service organizations. Blocs of lawmakers in the House of Representatives were afforded official resources to advance their policy agendas between 1979 and 1995. In the wake of the "Republican Revolution, " however, these groups were categorically dismantled. Using a difference-in-difference design, I estimate the individual-level effect of losing congressional resources on relative legislative effectiveness. The results inform our understanding of faction power, legislative bargaining and evolving congressional institutions.